2005
DOI: 10.1007/s10103-005-0339-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LLLT Ga–Al–As (685 nm) on LPS-induced inflammation of the airway and lung in the rat

Abstract: The purpose of this study was to investigate the effect of low level laser therapy (LLLT) on male Wistar rat trachea hyperreactivity (RTHR), bronchoalveolar lavage (BAL) and lung neutrophils influx after Gram-negative bacterial lipopolyssacharide (LPS) intravenous injection. The RTHR, BAL and lung neutrophils influx were measured over different intervals of time (90 min, 6 h, 24 h and 48 h). The energy density (ED) that produced an anti-inflammatory effect was 2.5 J/cm(2), reducing the maximal contractile resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 36 publications
4
39
0
4
Order By: Relevance
“…Generally, many studies indicated that, wounds irradiated by laser showed a reduction inflammatory reaction, started at the first post-operative day with a mild appearance of fibroblasts compared with control [14][15][16]. Many workers reported that laser irradiation inhibits inflammatory cells and cytokines liberation [17,18]. Kami [3] The Effect of Helium-Neon Laser, Using Different Methods and Frequencies of Radiation, on Wound Healing inflammatory effect of laser may up regulate angiogenesis around the wound causing an increase in blood flow, and thus promoter wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, many studies indicated that, wounds irradiated by laser showed a reduction inflammatory reaction, started at the first post-operative day with a mild appearance of fibroblasts compared with control [14][15][16]. Many workers reported that laser irradiation inhibits inflammatory cells and cytokines liberation [17,18]. Kami [3] The Effect of Helium-Neon Laser, Using Different Methods and Frequencies of Radiation, on Wound Healing inflammatory effect of laser may up regulate angiogenesis around the wound causing an increase in blood flow, and thus promoter wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…The irradiation period was set at 15 seconds per operative wound. The irradiation of 8.5 mW produced power density (PD) of 139 mW/cm 2 and energy density (ED) of 2.09 J/cm 2 , and irradiation of 17.0 mW produced PD of 281 mW/cm 2 and ED of 4.21 J/cm 2 were measured with a light power meter (TQ8212; Advantest, Tokyo, Japan). We assigned 5 rats to each of 11 groups: one group as a non-irradiation control, and ten irradiation groups which received either 8.5 mW or 17.0 mW of 15 seconds LLLT per operative wound a day with one of five different irradiation frequencies, i.e., daily (from the 1st to 6th day following surgery), every other day (the 1st, 3rd, and 5th day), on only the 1st day, on only the 3rd day, and on only the 5th day; the 1st day was the day following surgery.…”
Section: Methodsmentioning
confidence: 99%
“…69(8): 799-806, 2007 Low reactive level laser therapy (LLLT) [26] has been utilized clinically since the first successful cases reported by Mester [21][22][23]. Many studies have been published and various effects of LLLT have been reported such as (1) promotion of wound healing [3, 5, 14-19, 28, 29, 31-33], (2) alleviation of pain [4,7,32], (3) improvement in local circulation [20], and (4) alleviation of inflammation [2,7,8], and (5) bactericidal effects [12].In spite of this various fundamental questions have not yet been answered. Regarding wound healing, for example, it is not certain when LLLT should be performed following injury, or what level and frequency of irradiation is effective [35,36].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…O LBP vem sendo usado com o objetivo de promover efeitos analgésicos [4][5][6][7] , modulação da inflamação [8][9][10][11][12][13][14] , efeitos cicatriciais [15][16][17] e vasodilatadores locais 19 , sem os riscos de produção de calor e dano ao tecido irradiado 7,18,19 . A ação analgésica da laserterapia pode ser explicada a partir de algumas hipóteses: modulação dos processos inflamató-rios 3,9,20 , alteração da excitação e condução nervosa dos neurônios periféricos 21,22 , liberação de opioides endógenos 23,24 e aumento na síntese de serotonina 4,25 .…”
Section: Introductionunclassified